2016
DOI: 10.4236/jacen.2016.54018
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitocidal Activity of Extracts from <i>Ammi visnaga </i>(Apiaceae) Seeds

Abstract: Aedes aegypti mosquitoes are responsible for transmission of many viral diseases, such as Zika fever, dengue fever, yellow fever, and chikungunya. Emergence of resistance to currently used pesticides among mosquitoes has increased the importance for the search for novel mosquito control agents. Natural products, particularly plant and microbe derived secondary metabolites, are good sources in the search for such compounds. Ammi visnaga (Lam.) Lamarck is a plant in the Apiaceae family native to North Africa, Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…(Umbelliferae), caused L3 mortality (LC 50 192.1 μM) [ 140 ]. In another study, 83 demonstrated 100% larvae mortality at 3.84 μM and 75% adult mortality at 19.21 μM/mosquito for permethrin-susceptible strains [ 141 ]. Another furanochromone isolated from A. visnaga , visnagin ( 84 ) presented 93% mortality at 4.34 μM, together with moderate adulticidal activity (65% mortality at 21.72 μM/mosquito).…”
Section: Secondary Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…(Umbelliferae), caused L3 mortality (LC 50 192.1 μM) [ 140 ]. In another study, 83 demonstrated 100% larvae mortality at 3.84 μM and 75% adult mortality at 19.21 μM/mosquito for permethrin-susceptible strains [ 141 ]. Another furanochromone isolated from A. visnaga , visnagin ( 84 ) presented 93% mortality at 4.34 μM, together with moderate adulticidal activity (65% mortality at 21.72 μM/mosquito).…”
Section: Secondary Metabolitesmentioning
confidence: 99%
“…In addition, this study investigated 2 furanocoumarins isolated from Ruta graveolens L. Royle (Rutaceae): 5-methoxypsoralen (5-MOP) ( 85 ) and 8-methoxypsoralen (8-MOP) ( 86 ), which showed moderate adulticidal activity (55% mortality at 23.13 μM/mosquito and 67.5% mortality at 23.13 μM/mosquito, respectively). Compound 86 presented weak activity against L3 (53.3% mortality at 4.63 μM) while 85 was inactive [ 141 ].…”
Section: Secondary Metabolitesmentioning
confidence: 99%
“…In the search for effective and environmentally friendly mosquito control agents, we have examined natural sources such as microbes and plants and the synthetic analogs of natural products (Meepagala et al 2013, 2015, 2016, 2018). These plants and microbes have evolved in their ecological niches to produce defensive compounds against other competing organisms in their surroundings such as microbes, plants, and insects to enhance their survival.…”
Section: Introductionmentioning
confidence: 99%